The Pacific Ocean - Taylor, Leighton; Wu, Norbert (Woodbridge, Conn. : Blackbirch Press, 1998)
Text and photographs present some of what is known about the Pacific Ocean, its islands, its people, and its exotic creatures.
Includes index.
Includes glossary.
Includes bibliography.
4-8
AR Accelerated Reader
Keywords: Pacific Ocean -- Juvenile literature